ANALYSIS OF NATURAL AND SOCIAL SCIENCES LEARNING IN THE INDEPENDENT CURRICULUM WITH THE 2013 CURRICULUM SCIENCE AND SOCIETY LEARNING - M. Rofi Fauzi; Hafid Al Gifari (Waniambey: Journal of Islamic Education, 2025)
This study aims to analyse the differences in NSS learning in the independent curriculum, which was originally science and social studies learning in the 2013 curriculum. This study uses a literature research method. The results of the study show that the combination of science and social studies into NSS is essentially an effort by the ministry to improve the quality of education. There are several new terms in NSS learning, such as the existence of learning outcomes for each phase, which were previously learning competencies, and the existence of the Pancasila Student Profile Strengthening Project (P5). However, apart from these new terms, it seems that the ministry needs to look at things from a different angle. For example, the ministry should focus more on the welfare of teachers. It would be wiser for the ministry to strive to improve the welfare of teachers by working with honorary teachers from all schools in Indonesia to make them more prosperous, rather than having to create a curriculum renewal programme.